Reevaluating the Principle of Legal Fiction: Balancing Legal Certainty and Social Justice - Said, Muhtar; Fadli, Moh.; Widiarto, Aan Eko; Al-Uyun, Dhia (Journal of Indonesian Legal Studies, 2025)
The principle of legal fiction is widely recognized for its role in legitimizing laws and ensuring legal certainty. However, while it contributes to the stability and predictability of legal applications, it also has inherent weaknesses that may lead to unjust outcomes, particularly for vulnerable groups who are unaware of the law. In the context of Indonesia’s vast territory, the lack of widespread socialization and public awareness of new legal regulations exacerbates these issues. Consequently, individuals, especially from lower socioeconomic classes, may become inadvertently entangled in legal processes due to their ignorance of applicable laws, leading to potential injustices. The principle of legal fiction, therefore, may inadvertently serve as a tool of oppression, particularly when used to position suspects as defendants without adequate awareness or understanding of their legal rights. This paper argues for a re-evaluation and improvement of the principle to ensure a more just and transparent application. A more nuanced approach is needed, distinguishing between its absolute application in criminal cases and its non-absolute use in regulatory offenses. By refining the concept of legal fiction, we can enhance both its legitimacy and its capacity to uphold justice for all members of society.